Estrategias de marketing y la comercialización de los productos de la empresa Lincoln en la ciudad de Riobamba - Jessica Elizabeth, Paña Zavala (2020)
The present research is oriented to the strategies of marketing and the commercialization of the products of the LINCOLN company in the city of Riobamba. LINCOLN is a company dedicated to the manufacture of industrial equipment created in 1970 with the aim of promoting the national industry through its products and promoting the economic development of the Province of Chimborazo. The internal situation in which the company is currently found was studied and it was analyzed which are the errors that usually exist and the reason why its sales have been decreasing; subsequently, the internal processes on the positioning of the market and its clients were identified. On the other hand, the marketing strategies designed by those specialized in the field were studied with the aim that it can be implemented in the company based on its needs; and through these they can expand in the market, reach their customers in such a way that they increase their commercialization and meet the established objectives The method used in this research is the hypothetical deductive of descriptive type and non-experimental design; The target population of the study is made up of 523 people who correspond to the client portfolio and a sample of 222 was obtained; subsequently, an interview was conducted with the 15 employees of the company as a primary contribution to the study.The results obtained through the SPSS program were analyzed and the fundamental strategies for their development in the market were proposed, later it was finalized with the conclusions and recommendations for the present research.